Internal Communication and Employee Relations Management for Effective Staff Performance in Nigeria Customs Service - Abdullahi Aliyu Maiwada; Barth Oshionebo (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
In the contemporary global landscape, organizations have transitioned from conventional approaches to communication towards developing comprehensive communication strategies that center around employee motivation and engagement. This shift emphasizes the pivotal role of strategic internal communication, a relatively nascent but increasingly vital subject of study and application in the business world. The contemporary corporate environment observes a shift in employee roles, with employees increasingly undertaking responsibilities traditionally associated with public relations. Expectations of roles are pivotal in comprehending this transformation in PR practice, as expectations and norms greatly influence communication behavior and, consequently, organizational performance. Within this context, a content analysis of secondary data was done for the interpretation of the data. This allowed for the evaluation of existing knowledge for the purpose of relevance, consistency, replication and refutation. The paper argues that internal communication practices within paramilitary agencies, such as the Nigeria Customs Service, diverge from conventional corporate organizational models. This divergence is particularly pronounced given the agency's multifaceted role in revenue generation, the suppression of smuggling, trade facilitation, and other functions. The paper concludes that employee participation and job satisfaction played the mediating role in the relation between internal communication and job performance of the employees.